CASE STUDY ABOUT LOW STUDENT LEARNING MOTIVATION IN CLASS IV SDN 9 BALAESANG IN THE PANDEMY COVID 19 - Fitriani Fitriani; Arif Firmansyah; Herlina Herlina (Jurnal Dikdas, 2021)
The formulation of the problem in this study is what caused the low student motivation in Civics class IV SDN 9 Balaesang during the Covid 19 pandemic. The purpose of this study is to identify or trace and describe what causes the low student learning motivation in Civics in the classroom. IV SDN 9 Balaesang. The research design used is descriptive qualitative. using a questionnaire from 20 fourth grade students at SDN 9 Balaesang. Data collection techniques used were observation, questionnaires, and documentation. The results of this study were 20 grade IV students at SDN 9 Balaesang, from the results of research observations on the results tables of the fourth grade student respondents concluded that students' learning motivation was still lacking. There are obstacles during learning, including teachers who still do not understand students and the Covid 19 pandemic conditions that prevent students from learning in class. The conclusion of this study is the low student motivation caused by the lack of student motivation both from extrinsic and intrinsic motivation in class IV SDN 9 Balaesang during the Covid 19 pandemic, this can be seen in the results of student respondents in the existing data table.